2012
DOI: 10.1186/1471-2407-12-591
|View full text |Cite
|
Sign up to set email alerts
|

“Iron-saturated” bovine lactoferrin improves the chemotherapeutic effects of tamoxifen in the treatment of basal-like breast cancer in mice

Abstract: BackgroundTamoxifen is used in hormone therapy for estrogen-receptor (ER)-positive breast cancer, but also has chemopreventative effects against ER-negative breast cancers. This study sought to investigate whether oral iron-saturated bovine lactoferrin (Fe-Lf), a natural product which enhances chemotherapy, could improve the chemotherapeutic effects of tamoxifen in the treatment of ER-negative breast cancers.MethodsIn a model of breast cancer prevention, female Balb/c mice treated with tamoxifen (5 mg/Kg) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 55 publications
0
28
0
1
Order By: Relevance
“…Astrocytes that divide from immature precursor cells may intervene actively in DA cell demise in this culture paradigm (Mourlevat et al, 2003), suggesting that the protective effect of lactoferrin against the spontaneous loss of DA neurons may possibly result from an indirect effect on dividing glial cells. Also in support of this possibility, lactoferrin was reported to inhibit the growth of some cancer cells (Zemann et al, 2010;Tung et al, 2013) and to improve the therapeutic effects of anticancer therapies (Sun et al, 2012). Hence, we wished to determine whether the proliferation rate of astrocytes or their precursor cells (both cell populations represent more than 95% of dividing cells at this stage of the cultures) was affected by Lf in midbrain cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Astrocytes that divide from immature precursor cells may intervene actively in DA cell demise in this culture paradigm (Mourlevat et al, 2003), suggesting that the protective effect of lactoferrin against the spontaneous loss of DA neurons may possibly result from an indirect effect on dividing glial cells. Also in support of this possibility, lactoferrin was reported to inhibit the growth of some cancer cells (Zemann et al, 2010;Tung et al, 2013) and to improve the therapeutic effects of anticancer therapies (Sun et al, 2012). Hence, we wished to determine whether the proliferation rate of astrocytes or their precursor cells (both cell populations represent more than 95% of dividing cells at this stage of the cultures) was affected by Lf in midbrain cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, hLf and bLf have been shown to exert anti-cancer activity for both tumor prevention and treatment [18,109]. The Lf preventive effect has been demonstrated in several animal models bearing different types of tumors, including lung, tongue, esophagus, liver, and colorectal [110][111][112][113], whereas Lf treatment was found efficient in inhibiting growth, metastasis, and tumor-associated angiogenesis [18,114,115], as well as in boosting chemotherapy [116,117].…”
Section: Lactoferrin and Cancermentioning
confidence: 99%
“…In particular, lactoferrin, a whey protein, has been demonstrated, in vitro , to inhibit the growth of breast cancer (MDA‐MB‐231) and nasopharyngeal carcinoma cells by, respectively, arresting the cell cycle at the G1/S transition and suppressing Akt signalling (Damiens et al , ; Deng et al , ). Studies in mouse model in vivo confirmed its anticancer activity against head‐and‐neck squamous cell carcinoma (Varadhachary et al , ) and demonstrated an improvement in the chemotherapeutic effects of tamoxifen in 4 T1 breast cancer (Sun et al , ).…”
Section: Methodsmentioning
confidence: 94%